2021
DOI: 10.1155/2021/1697070
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐Linked Irisin Prevents Mortality and Enhances Cognition in a Mice Model of Cerebral Ischemia by Regulating Klotho Expression

Abstract: Irisin, which can be released in the hippocampus after physical exercise, is demonstrated to have beneficial effects on neurovascular diseases. This study investigated the impact of exercise linked-irisin on mortality and cognition in a mice model of cerebral ischemia and further explored its underlying mechanism. The cerebrospinal concentrations of irisin and klotho from ischemic stroke patients were measured with an enzyme-linked immunosorbent assay (ELISA). The cognitive function of mice was evaluated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In 27 articles, data was discussed but not shown. Only 56 studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 71 ] were included in this meta-analysis ( Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…In 27 articles, data was discussed but not shown. Only 56 studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 71 ] were included in this meta-analysis ( Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that deletion of Fndc5/irisin impaired hippocampal neurogenesis and cognitive function in exercise and AD, 49 and peripheral administration of irisin improved cognitive impairment after cerebral ischemia. 50 Herein, we identified irisin as a novel target of NK, which mediated the beneficial effects of NK on the brain.…”
Section: Discussionmentioning
confidence: 98%
“…In healthy middle-aged adults, endurance, or resistance exercise boosts plasma klotho levels both acutely and chronically (Matsubara et al, 2014;Santos-Dias et al, 2017;Tan et al, 2018;. When looking at the underlying mechanisms of exercise, Jin et al demonstrated that irisin, an exercise-derived myokine, enhances mortality and cognition in mice after cerebral ischemia through upregulation of klotho (Jin et al, 2021). This positive effect of exercise and irisin is abolished in klotho-knockout mice (Jin et al, 2021).…”
Section: Exercise Upregulates Klothomentioning
confidence: 99%